The factors that influence the perception of cyber bullying among teenagers: a case study at Piasau Jaya, Miri, Sarawak / Ignatius Nyalayang Beti and Intan Rosleza Rusli - Beti, Ignatius Nyalayang; Rusli, Intan Roslez (2014)
In today’s world everyone use technology more than ever. Young people are extremely intelligent users of technology and frequently lead the method in adapting new technologies to everyday use. With high speed of internet access, which they can use to interact through virtual world such as posting blogs and videos, keep personal profiles on social networking websites, share photos and more that they didn’t even realize that they have commit cyber bullying. Technology, specially the internet permits us to gain instant and fast information. The wise usage of the internet can actually build a knowledgeable person, advance in information and informative teens who will always keep update with the current situation. But it can also be the other way around when the teenagers starts to misuse it as according to Effendy Ibrahim, Symantec's Norton Business which led for Asia South Region. In Malaysia, 60 cases of cyber bullying were reported to Cyber Security Malaysia as of October 2007 (McKenna, n.d) Cyber bullying can be defined as a means of indirect aggression in which peers use electronics medium to criticize, offence, threaten and harass a peer (Raskauskas & Stoltz, 2007). Technology has allowed teens to take the bullying that thrives in school into cyberspace. Young people nowadays are more comfortable in using the online technology as a medium to communicate and keep in touch (O’Brien, 2010). In practice, cyber bullying behaviours are similar to indirect forms of traditional bullying such as harassing and threatening others but they are slightly different because cyber bullying involves the interaction through virtual world while traditional bullying involves physical